Moving beyond annual data reports: A blueprint for communicating and disseminating actionable intelligence. Issue 1 (10th May 2022) - Ruiz, Raquel; Schwartz, Ann; Orlando, Elissa; Ossip, Deborah; Zand, Martin S.; Dozier, Ann
Abstract: Identifying and disseminating actionable intelligence is a challenging task that requires thoughtful planning. The National Center for Advancing Translational Sciences instituted the Common Metrics Initiative with the goal of evaluating the Clinical and Translational Science Awards (CTSA) Programs using a standard set of metrics. Initially managed by Tufts University, the Center for Leading Innovation and Collaboration (CLIC) at the University of Rochester began leading this initiative in 2017. In directing this work, CLIC created a framework for communicating and disseminating data insights. Insights to Inspire emerged from the need to share strategies and lessons learned to improve metric performance at the local level to a network of 60+ academic research institutions. Insights to Inspire employs a mixed methods approach for translating data into actionable intelligence. A series of blogs, webinars, and webcasts were designed to communicate metric-specific strategies used by individual sites to the broader CTSA consortium. A dissemination plan to expand the reach beyond metric stakeholders utilized focused communications including social media channels, network newsletters, and presentations at national meetings. This framework serves as a blueprint for other national evaluation programs interested in a systematic approach to using data insights for continuous improvement.